Effectiveness of Contraceptive Counseling in Perinatal Period - Allawat, Zara; Zia, Mohsina Saeed; Sajjad, Nadia; Abbasi, Rashna Khan; Alim, Nahida; Hameed, Nafeesa (Indus Journal of Bioscience Research, 2025)
Background: Contraceptive counseling during the perinatal period plays a crucial role in reducing unintended pregnancies, particularly in women with higher parity. However, the efficacy of contraceptive counseling remains under investigation, with varying success across different demographic groups. Objective: To determine the efficacy of contraceptive counseling in perinatal period at AIMS hospital Azad Jammu and Kashmir. Study Design: Descriptive study. Duration and Place of Study: The study was conducted from May 2024 to May 2025 at the Department of Obstetrics and Gynaecology, AIMS Hospital, Muzaffarabad, AJK. Methodology: A total of 196 women aged 20–40 years, married, with a parity of ≥4, and in the perinatal period were included in the study. Participants were counseled on one of the following contraceptive methods: male condoms, emergency contraceptive pills, oral contraceptive pills, injectable contraceptives, or IUCD. After 12 months, the efficacy, defined as no unintended pregnancies, was evaluated. Results: The mean age of participants was 31.2 ± 4.6 years, with a mean parity of 5.6 ± 1.1. Among participants, 67.9% reported contraceptive counseling efficacy, while 32.1% did not. Stratified analysis revealed that efficacy was significantly associated with the perinatal period, socioeconomic status, parents’ education, residential status, and contraceptive method type. Postpartum women and those from higher socioeconomic classes had higher efficacy. IUCD users reported 100% efficacy, while injectable contraceptive users had an efficacy of 91.7%. Conclusion: Contraceptive counseling during the perinatal period is effective in preventing unintended pregnancies, with efficacy varying across different demographic factors and contraceptive methods.